Public Investment Management in Health Care in the ICU (Observatorio Económico, 2015)
The use of concessions is one of the major subsidiary policies that the Concertación governments  (Chile's center-left coalition, 1990–2010) designed to provide certain public goods such as transportation, highways, prisons, ports, airports, and hospital construction. Under this policy, private firms take charge of the investment in and maintenance of these goods for a given period of time, in exchange for State subsidies or direct payments from consumers, as occurs in the case of highways. Continue reading...
Keywords: Health; Public Investment; Concessions; ICU